Kajian Tampilan Arsitektur Simbolik pada Taman Budaya Jawa Timur - Muhammad Alfian Firmansyah; Ami Arfianti (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
The cultural center is a place used to accommodate all arts and culture activities. The East Java Cultural Park is a building complex designed to promote and preserve East Javanese culture. In appearance, the East Java Cultural Park at first glance applies the Javanese architectural style. However, in this building it is not yet known to what extent the Javanese architectural appearance was used. This research was conducted to identify the Javanese architectural appearance of the TBJT building. Qualitative research using a descriptive critical method approach was applied to this research. Data was collected through direct observation, interviews and analysis of literature related to the application of Javanese architectural symbolism in TBJT. The results of this research are that TBJT has a symbolic meaning in Javanese architecture which can be seen from the appearance of the TBJT building. However, this application does not fully follow the rules of Javanese architectural appearance because there is an amalgamation of other styles, namely colonial architecture. It is hoped that this research can provide a deeper understanding of the application of Javanese architectural symbolism to the appearance of the East Java Cultural Park.